انفكاك الجهة عند الأصوليين - ويردي, مشتاق علي الله (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
This academic work explores the concept of Infikak al-Jiha (Separation of Perspectives) as one of the most important usulī (fundamental jurisprudential) principles that facilitates understanding the multiplicity of legal rulings related to a single act from various angles. The study addresses the definition of this principle in both linguistic and technical terms, emphasizing its significance in usul al-fiqh through an examination of its evidences drawn from the Qur'an, the Prophetic Sunnah, and the statements of the Companions. This usulī study analyzes the concept of Infikak al-Jiha in Islamic jurisprudence by exploring multiple dimensions of this issue, which has profound implications for the usulī understanding of legal rulings in different contexts. The research opens a broad avenue for exploring the relationship between acts of worship and the actions of legal incumbents in various conditions, whether temporal, locational, or based on gender, aiming to disentangle these relationships through the usulī methodology in order to rectify the understanding of complex legal situations. The study further delves into how the scholars of usul al-fiqh have defined Infikak al-Jiha and its applications, asserting its fundamental presence in Islamic legislation through Qur'anic verses, Prophetic traditions, and the actions of the Companions. Additionally, the research addresses the issues of Infikak al-Jiha concerning time, place, and gender, analyzing how the usulī scholars have treated the separation of perspectives through these dimensions.